2014
DOI: 10.1371/journal.pone.0096867
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Retention in Pre-ART Care in Cape Town, South Africa

Abstract: BackgroundFew studies have evaluated access to and retention in pre-ART care.ObjectivesTo evaluate the proportion of People Living With HIV (PLWH) in pre-ART and ART care and factors associated with retention in pre-ART and ART care from a community cohort.MethodsA cross sectional survey was conducted from February – April 2011. Self reported HIV positive, negative or participants of unknown status completed a questionnaire on their HIV testing history, access to pre-ART and retention in pre-ART and ART care.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Antiretroviral treatment (ART) initiation when HIV disease is advanced is associated with poor treatment outcomes and high mortality rates [1, 2]. Current international guidelines call for universal test and treat (UTT), ART initiation irrespective of CD4 count [3].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral treatment (ART) initiation when HIV disease is advanced is associated with poor treatment outcomes and high mortality rates [1, 2]. Current international guidelines call for universal test and treat (UTT), ART initiation irrespective of CD4 count [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Overall 46 studies [2,20‐24,26‐30,32,40,43,45,49‐51,53,61,63,65,68,69,72,74‐94] reported on retention on ART or being on ART and 34 (74%) provided clear definitions of numerators and denominators. The majority of studies were longitudinal (29 studies, 63%), 13 were cross‐sectional and four of mixed design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations